An Exploratory Study Of Accounting On Ijarah As Practiced By Malaysian Financial Institutions - Shariff, Ros Aniza Mohd; Abdul Rahman, Abdul Rahim (The International Journal of Accounting and Business Society, 2005)
Prior studies on Ijarah were mainly focusing on the economics, legal and ï¬nancial aspects, there was, however, so far no in- depth study on accounting for Ijarah. The main objective of this study is to explore the nature of accounting practices as practiced by Malaysian ï¬nancial institutions. First, the study makes comparison between the Intemational Accounting Standard on leasing (IAS 17); the accounting standard for Ijarah (FAS 8) as developed by the Accounting and Auditing Organization for lslamic Financial Institutions (AAOIFI); and the Malaysian Accounting Standard Board (MASB 10). The study found that there are major differences as to the nature of leasing and Ijarah, and as a result accounting principles that have driven all the three standards as well as accounting techniques developed for leasing and Ijarah are signiï¬cantly different. Secondly, the study examines the level of acceptability of the AAOlFIâ€™s FAS 8 among the Malaysian ï¬nancial institutions. The result of the questionnaire survey shows a low level of acceptability of FAS 8 and the result from the interviewsurvey further conï¬rms this ï¬nding. This study indicates, subject to further studies on other lslamic ï¬nancial instruments and other lslamic countries, that the effort to harmonise the accounting practices on lslamic ï¬nancing practices by ï¬nancial institutions internationally may be a difficult task. Secondly, until and unless the AAOIFI standard is adopted by the regulatory agency as in the case of Malaysia, Bank Negara Malaysia, AAOIFI standards will remain only as a reference but do not have the legal authority. Consequently, the quality and comparability of accounting information of lslamic ï¬nancing such as Ijarah will be seriously at a stake.